The excess body fat is a potential mediator between consumption of ultra-processed foods and cardiometabolic risk in normal-weight Brazilian children - Cota, Bruna Clemente; Juvanhol, Leidjaira Lopes; Filgueiras, Mariana de Santis; Pereira, Patrícia Feliciano; de Novaes, Juliana Farias (Frontiers in Nutrition, 2026)
Background/objectiveStudies indicate an association between the consumption of ultra-processed foods (UPF) and cardiometabolic risk; however, this relationship is still unclear in normal-weight children, and it is not yet known whether the Normal-Weight Obesity (NWO) phenotype may be a mediator between this relationship. We aimed to evaluate the mediating role of the NWO phenotype in the association of UPF consumption with cardiometabolic risk factors.MethodsThis cross-sectional study was carried out with 242 normal-weight children aged 8 to 9 y in Viçosa, Minas Gerais, Brazil. Cardiometabolic risk was assessed as a latent variable using the following indicators: homeostatic model assessment for insulin resistance (HOMA-IR), leptin, mean arterial pressure (MAP), and waist circumference (WC). Three 24-h dietary recalls were performed to evaluate NOVA classification groups. The NWO phenotype was defined as normal-weight according to body mass index and high body fat assessed by dual-energy x-ray absorptiometry. A structural equation model was used to test direct and indirect associations.ResultsWe found a direct association of UPF consumption [SC (standardized coefficient): −0.193, p = 0.02] and the NWO phenotype (SC: 0.819, p < 0.001) with cardiometabolic risk; as well as between UPF consumption and the NWO phenotype (SC: 0.212, p = 0.03). In addition, an indirect association was observed between UPF consumption and cardiometabolic risk, being mediated by the NWO phenotype (SC: 0.174, p = 0.04).ConclusionOur findings indicate the potential influence of excess body fat on the pathway between UPF consumption and cardiometabolic risk in children with adequate BMI/age.